2008
DOI: 10.1210/jc.2007-2522
|View full text |Cite
|
Sign up to set email alerts
|

Association of the Metabolic Syndrome with Severe Periodontitis in a Large U.S. Population-Based Survey

Abstract: Severe periodontitis is associated with metabolic syndrome in middle-aged individuals. Further studies are required to test whether improvements in oral health lead to reductions in cardiometabolic traits and the risk of metabolic syndrome or vice versa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
283
3
9

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 252 publications
(315 citation statements)
references
References 37 publications
20
283
3
9
Order By: Relevance
“…We [4,17,18] and others [3] have demonstrated the influence of gut microbiota on metabolic disease in animal models. Consistently, in humans, periodontitis, a chronic gram-negative infectious disease of the oral cavity, has been associated with the metabolic syndrome [19][20][21][22][23]. In line with these data, the longitudinal study reported here provides for the first time evidence of the involvement of tissue microbiota in the development of diabetes in humans.…”
Section: Discussionsupporting
confidence: 86%
“…We [4,17,18] and others [3] have demonstrated the influence of gut microbiota on metabolic disease in animal models. Consistently, in humans, periodontitis, a chronic gram-negative infectious disease of the oral cavity, has been associated with the metabolic syndrome [19][20][21][22][23]. In line with these data, the longitudinal study reported here provides for the first time evidence of the involvement of tissue microbiota in the development of diabetes in humans.…”
Section: Discussionsupporting
confidence: 86%
“…The positive correlation between Acute Coronary Syndrome and inflammatory markers such as CRP, IL-1, IL-6, TNF-α was observed [10,11]. In blood plasma or serum it is possible to assess the concentration of inflammatory markers, such as Interleukin 6 (IL-6) and C-reactive protein (hs-CRP, highsensitivity C-reactive protein).…”
Section: Inflammatory Markersmentioning
confidence: 99%
“…In blood plasma or serum it is possible to assess the concentration of inflammatory markers, such as Interleukin 6 (IL-6) and C-reactive protein (hs-CRP, highsensitivity C-reactive protein). These markers are useful to identify people with high risk of Incident Cardiovascular Events [10][11][12][13][14]. Cytokines are the mediators of inflammatory process and immune response in human body.…”
Section: Inflammatory Markersmentioning
confidence: 99%
“…Various cross-sectional and case-control studies have found a strong association between obesity and periodontal disease (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). It has also been revealed that metabolic syndrome increases the risk of periodontitis, suggesting that people exhibiting several components of metabolic syndrome should be encouraged to undergo regular periodontal examination (7,13,14,(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…It has also been revealed that metabolic syndrome increases the risk of periodontitis, suggesting that people exhibiting several components of metabolic syndrome should be encouraged to undergo regular periodontal examination (7,13,14,(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%